Research on the Structural Relationship of Online Persistent Purchase of Museum Cultural and Creative Products in the Context of Digitalization - Lin, Mengyi; Meng, Zhaoyang; Luo, Caisheng (Frontiers in Psychology, 2022)
With the development and support of modern technologies such as digital media and online live stream, it has become an important solution and an effective way to promote the online transaction of museum cultural and creative products. With the aim of ensuring the existence and sustainability, research on the influencing factors of online consumers' persistent purchase has guiding and referential significance for promoting the innovation and operation of online museum cultural and creative products. Based on the Technology Acceptance Model combined with the Post-Acceptance Model of Information System Continuance and the theories on customer satisfaction index, this research introduces perceived interest and media richness as variables and constructs a model of the influencing factors of online consumers' persistent purchase of museum products. The research model and related hypotheses were verified through Structural Equation Modeling (SEM). The research found that perceived value and satisfaction are the key variables that have impact on the persistent purchase of consumers. Perceived quality, brand trust, media richness, perceived interest and perceived usefulness have significant effects on perceived value and satisfaction. Involvement in purchasing decisions positively moderates the impact on satisfaction of perceived value. The conclusion can be referred to for operators and product developers.